2009
DOI: 10.1007/s00284-008-9341-3
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study on the Correlation Between Oral Helicobacter pylori and Gastric H. pylori

Abstract: The current study was conducted to determine the prevalence of Helicobacter pylori in the oral cavity of a Chinese population. Nested polymerase chain reaction (PCR) was used to investigate whether individuals with oral H. pylori show more possibility of gastric infection and to examine the relationship between gastric H. pylori infection and the presence of the bacteria in the oral cavity. A total of 443 dyspeptic patients participated in the study. Gastric H. pylori infection was detected by the rapid urease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 19 publications
3
38
0
2
Order By: Relevance
“…Song et al (2000) analysed 117 samples of dental plaque from 42 patients and verified the presence of the bacterium in 68% of the samples. These results are similar to those of Liu et al (2009), who found positive samples in 59% of their subjects. It is interesting to note that these studies differ from the results of Kignel et al (2005), who found a low prevalence in gastric biopsy samples and only one positive dental plaque sample.…”
Section: Detection Of H Pylori In Saliva and Dental Plaque By Southesupporting
confidence: 80%
“…Song et al (2000) analysed 117 samples of dental plaque from 42 patients and verified the presence of the bacterium in 68% of the samples. These results are similar to those of Liu et al (2009), who found positive samples in 59% of their subjects. It is interesting to note that these studies differ from the results of Kignel et al (2005), who found a low prevalence in gastric biopsy samples and only one positive dental plaque sample.…”
Section: Detection Of H Pylori In Saliva and Dental Plaque By Southesupporting
confidence: 80%
“…We could not study the effect of triple drug regimen on gHP / oHP positivity, but we observed a much higher prevalence of oHP in our study (63.6% vs. 35%). Liu et al (16) conducted nested PCR study on dental plaques and RUT plus antral biopsy for detection of oHP and gHP respectively, in 443 dyspeptic patients. oHP was found in 59.4% and gHP in 61.6 %.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism is an increased consumption of platelets inside utero-placental circulation [7,8] accelerating thrombopoiesis in bone marrow. As a result, an increase in mean platelet volume (MPV), platelet distribution width and large-size platelets in peripheral film were observed in many [7,9,17,25] but not all reports [18,26]. Large-sized platelets may be pathogenic [27] but since platelet turnover is usually normal [20] and platelet count is low therefore, overall effect is a balanced platelet mass [7].…”
Section: Quantitative Changes In Plateletsmentioning
confidence: 99%